2015
DOI: 10.1139/cjz-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and catecholamine responses to social context and a chemical alarm signal in juvenile lake sturgeon,Acipenserfulvescens

Abstract: We examined potential benefits of group living in juvenile lake sturgeon (Acipenser fulvescens Rafinesque, 1817) and whether those benefits applied equally to associations with conspecific and allospecific individuals. In the first experiment, one focal lake sturgeon was placed with either seven size-matched conspecifics, allospecifics, or in isolation and given a 30 s air exposure. In the second experiment, one focal lake sturgeon was placed with either seven conspecifics or in isolation and was exposed to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…2; M-W U = 0, p < 0.001) indicates that the process of behavior recording is in itself stressful, and exposure to CSE is an additional stressor. Activation of the primary stress response pathway in reaction to CSE exposure, as seen in medaka, has also been reported in many other species4142435152. There are examples, however, ( Brycon cephalus and Rhamdia quelen ) where conspecific injury elicits an anti-predator behaviour, but cortisol changes are undetectable5354.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…2; M-W U = 0, p < 0.001) indicates that the process of behavior recording is in itself stressful, and exposure to CSE is an additional stressor. Activation of the primary stress response pathway in reaction to CSE exposure, as seen in medaka, has also been reported in many other species4142435152. There are examples, however, ( Brycon cephalus and Rhamdia quelen ) where conspecific injury elicits an anti-predator behaviour, but cortisol changes are undetectable5354.…”
Section: Discussionmentioning
confidence: 76%
“…Cortisol levels change via activation of the hypothalamus-pituitary-interrenal axis and peak within 15 minutes3940. Exposure to CSE can be a stressful event for some fish414243. I asked if behavioral changes in experimental subjects, described above, is accompanied by changes in cortisol levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This level is upregulated in the course of their maturation, indicating to necessity of being in permanent state of activity and alertness to confront possible aggression [35]. Moreover, in the model experiments with artificial upregulation of noradrenergic system in the brain structures, linear correlation between level of noradrenalin in the brain and level of social avoidance was revealed [35,36]. In the juveniles, bred in the pools, in conditions of food abundance and lack of predators, low levels of noradrenalin in the brain, really suppressing completely the state of alertness and reaction of escape from predators, are noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Need in socialization and defence against aggression in this age in the sturgeons are considered as secondary issues [35] and, first of all, in this case changes of the level of salinity and hydrodynamic regime of living milieu have mostly their effects [46][47][48][49]. So, our studies have shown that while breeding of sturgeon fishes of certain region under the hatchery conditions, their biological peculiarities of development in natural conditions should be taken into consideration and it is important to reveal critical periods of formation of the most important physiological functions of the organisms and input of environmental factors in these processes.…”
Section: Discussionmentioning
confidence: 99%